2020
DOI: 10.1098/rsos.191653
|View full text |Cite
|
Sign up to set email alerts
|

Calculation on surface energy and electronic properties of CoS 2

Abstract: Density functional theory was employed to investigate the (111), (200), (210), (211) and (220) surfaces of CoS 2 . The surface energies were calculated with a sulfur environment using first-principle-based thermodynamics. It is founded that surfaces with metal atoms at their outermost layer have higher energy. The stoichiometric (220) surface terminated by two layer of sulfur atoms is most stable under the sulfur-rich condition, while the non-stoichiometric (211) surface terminated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Our results indicate that the (100) orientation with a stoichiometric ratio termination has the lowest surface energy (0.284 J/m 2 ), followed by the (210) orientation (0.419 J/m 2 ). Interestingly, while previous studies have systematically investigated the surface stability of pyrite FeS 2 , and CoS 2 , the surface energy of c - CuS 2 had not been reported so far. Therefore, this study provides a valuable complement to the surface science of pyrite-type compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that the (100) orientation with a stoichiometric ratio termination has the lowest surface energy (0.284 J/m 2 ), followed by the (210) orientation (0.419 J/m 2 ). Interestingly, while previous studies have systematically investigated the surface stability of pyrite FeS 2 , and CoS 2 , the surface energy of c - CuS 2 had not been reported so far. Therefore, this study provides a valuable complement to the surface science of pyrite-type compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the irregular shape of the NPs, especially some of the NPs had a quasi-spherical shape, the (001) and ( 111) faces may also be exposed on the surface. 36 In addition, the electron paramagnetic resonance (EPR) spectrum of O-doped CoS 2 NPs indicated that there were no sulfur vacancies in them (Fig. S4 †).…”
Section: Resultsmentioning
confidence: 99%
“…With an increased amount of oxygen doping, the edges of the NPs showed a tendency to lose their angles between different exposed surfaces. As the quasi-spherical NPs with mainly exposed facets of (001) and (111), 36 and the surface energy of (001) facet is lower than that of (111) facet, 42 the DFT calculation uses (001) facet as the model is reasonable.…”
Section: The Pod-like Mechanism Of O-doped Cos 2 Npsmentioning
confidence: 99%